MODEL PELAYANAN RUMAH SAKIT BERBASIS KARAKTERISTIK SOSIAL EKONOMI MASYARAKAT UNTUK MENINGKATKAN KEPUASAN PASIEN - rita rahmawati (Jurnal Sosial Humaniora, 2010)
In long term, the research is aimed to improve hospital patients’ satisfaction in Bogor, Cianjur and Sukabumi Districts through the implementation of health care model based on socio economical characteristic of the community. Specific target of the research is to establish public health services based on socio economical characteristics of the community. The research was conducted by qualitative methods; data were obtained through by literature study, in-depth interviews, community satisfaction survey, Focus Group Discussion, and workshop. This research is aimed to gain understanding on public health services, i.e.: dominant factors affecting health services, patients’ need, issues related to disappointed or dissatisfied patients who were shifted to other hospitals.Results showed that there is inadequate satisfaction experienced by patients on health services provided by hospitals. The service is perceived by patients as slow; having low level of accuracy; having complicated services schedule and procedures; having low level of doctors’ understanding and skill in diagnosing illness. Patients’ satisfaction was influenced by patients’ personal and situational factors. Therefore, in order to increase patients’ satisfaction, it is recommended that a model of hospital services based on socio-economical characteristics of the community be adopted.